2019
DOI: 10.1007/s00125-019-04983-x
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in AIM2 induces inflammation and adipogenesis in white adipose tissue leading to obesity and insulin resistance

Abstract: Aims/hypothesis Absent in melanoma 2 (AIM2) is a cytosolic sensor for double-stranded DNA and a tumour suppressor. Binding of double-stranded DNA to AIM2 forms the AIM2 inflammasome, leading to activation of caspase-1 and production of IL-1β and IL-18. Although inflammasome-independent effects of AIM2 have been reported, its role in energy metabolism is unknown. We aimed to evaluate the effect of AIM2 in energy metabolism and glucose homeostasis. Methods Male and female whole body Aim2 knockout (Aim2 −/−) mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 52 publications
5
35
0
Order By: Relevance
“…We found that the year of publication, geographic region, study sample size, BMI, and gestational age were not sources of heterogeneity across the included studies. The binding of chemerin to its receptors can promote the recruitment of macrophages and dendritic cells, and neutrophil activation to produce inflammation [39], and chronic low-grade inflammation has been associated with increased IR [40]. A reduction in chemerin levels may be associated with the development of GDM through decreased insulin sensitivity and attenuated anti-inflammatory capacity [25].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the year of publication, geographic region, study sample size, BMI, and gestational age were not sources of heterogeneity across the included studies. The binding of chemerin to its receptors can promote the recruitment of macrophages and dendritic cells, and neutrophil activation to produce inflammation [39], and chronic low-grade inflammation has been associated with increased IR [40]. A reduction in chemerin levels may be associated with the development of GDM through decreased insulin sensitivity and attenuated anti-inflammatory capacity [25].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the NLRP3 function, deficiency in AIM2 increases inflammation and adipogenesis leading to spontaneous obesity and insulin resistance. 195 Correspondingly, Aim2 −/− mice were more obese than their WT counterparts and exhibited reduced energy expenditure and higher glucose intolerance. 195 196 AIM2 is also a regulator of hepatic fat levels.…”
Section: Aim2 Inflammasome Mediates Complex Functions In Metabolic mentioning
confidence: 98%
“…195 Correspondingly, Aim2 −/− mice were more obese than their WT counterparts and exhibited reduced energy expenditure and higher glucose intolerance. 195 196 AIM2 is also a regulator of hepatic fat levels. Deficiency in Aim2 resulted in liver enlargement with increased lipid deposition.…”
Section: Aim2 Inflammasome Mediates Complex Functions In Metabolic mentioning
confidence: 98%
“…Together, these studies suggest that AIM2 inflammasome activation might contribute to inflammation and the progression of NAFLD to NASH. On the other hand, AIM2-deficient ( Aim −/− ) mice showed spontaneous increase in body weight, fasting glucose, and insulin levels compared with wild type (WT) controls [ 50 ]. This was coincident with increased macrophage infiltration and pro-inflammatory markers in the white adipose tissue.…”
Section: Aim2 In Liver Diseasementioning
confidence: 99%